The Concept of Corporate Social Responsibility and Social Enterprise: The Pursuit of Social Responsibilities in Business Practise - Ardian Firmansyah (Business and Human Rights Law & Policy, 2025)
Corporate Social Responsibility (CSR) emphasizes addressing social and environmental issues often neglected by corporations. In the modern era, CSR has evolved to align with strategic management and corporate governance, guiding businesses toward ethical and sustainable practices. It contributes to economic development by supporting government efforts to boost per-capita income. However, critics argue that CSR has yet to reach its full potential. A key concern is the conflict between profit generation and social responsibility. Economist Milton Friedman asserts that CSR's focus on societal issues undermines a company's primary goal of generating income. Additionally, the legal framework for CSR remains weak. For example, the United Kingdom's Companies Act 2006 provides limited guidance, with no explicit provisions mandating CSR. This legal gap underscores the need for stronger legislative backing to enhance CSR's effectiveness and relevance. Social enterprises present a potential advancement of CSR principles. These organizations prioritize creating social impact over generating profits for shareholders, integrating community welfare into their core operations. In Europe, social enterprises demonstrate CSR at an advanced level, promoting sustainable social and economic growth. This research examines CSR's benefits for companies, the impact of legal reforms on enhancing its effectiveness, and the relationship between CSR and social enterprises. It explores whether aligning CSR with community welfare and corporate profitability is achievable. The study also investigates how a legal framework supporting CSR can ensure its significance in balancing business goals with societal responsibilities.